Editor's choice Water Extract of Tamarix gallica L. as effective Agents against C6 and HeLa tumor cell lines - Fellah Ouroud 1, 2, 3; Hameurlaine Samir; Djermane Mohamed; Tahar Wafa; et al (De Gruyter Poland Bogumiła Zuga 32A Str. 01-811 Warsaw, Poland, 2019)
The aerial parts of Tamarix gallica L. taken from three different climatic stages in Algeria (Oum El Bouaghi: Semi-arid, ElTaref: Humid, and Ouargla: Arid) were extracted using boiling distilled water. The crude extracts were subjected to total phenolics and flavonoids quantifications in addition to anti-proliferative assessment against two tumor cell lines namely rat brain tumor (C6) and human cervix carcinoma (HeLa) using BrdU (bromo-deoxyuridine) ELISA(Enzyme-linked immune-sorbent assay) and xCELLigence assay. The total phenolics yield was found to range between 16.14 and 39.32 mg GAE (Gallic acid equivalent)/g of extract and a flavonoids yield ranging between 16.51 and 20.35 mg QE(quercetin equivalent)/g of extract. The various phenolics were identified using HPLC-TOF/MS to highlight hesperidin and rosmarinic Acid as major components. Moreover, the extracts exhibited different levels of antitumor potency against C6 and HeLa cell lines depending upon the climatic stage and the concentration. A good cytotoxic effect was recorded with the species collected from the humid region at 250 µg/mL. On the contrary, the other extracts revealed a weak activity for both tests.